Anthropogenic Transformation and the Possibility of Renaturalising Small Rivers and Their Valleys in Cities – Łódź and Lviv Examples - Kobojek, Elżbieta (European Spatial Research and Policy, 2015)
Rivers used to serve important functions in the development of cities, and river valleys are a part of the urban space. Regardless of several centuries of anthropogenic influences large rivers and their valleys have remained the dominant elements of the cityscape. In the case of small rivers and valleys the situation has been different. The expansion of urban infrastructure often led to an elimination of rivers and their valleys from the developed area. In many cases rivers were directed down straightened concrete ditches and sometimes the locations of their channels were changed altogether. In the city centre, rivers were locked in underground channels, i.e. they vanished from the cityscape. Urban floods, so annoying for the inhabitants, usually occur within river sections which have been utilized intensively and covered with impermeable surface. Even though a river was hidden in underground interceptor pipes, a valley dip remains still accumulating rainfall. The aim of this article is to present the extent of transformation of small rivers and valleys within two large cities located on watersheds: Łódź and Lviv, and the contemporary utilization and the possibility of renaturalising them.